2016
DOI: 10.5664/jcsm.5688
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Disordered Breathing with Wake-Up Acute Ischemic Stroke: A Full Polysomnographic Study

Abstract: Study Objectives: Sleep disordered breathing (SDB) is a frequent comorbidity in stroke patients. SDB is one of the independent risk factors for ischemic stroke. Conversely, stroke may contribute to SDB onset or aggravate premorbid SDB. Multiple mechanisms underlying SDB might be responsible for the development of stroke. The aim of this study was to compare polysomnographic, clinical, and laboratory characteristics of wake-up (WUS) and non-wake-up acute ischemic strokes (NWUS). Methods: We prospectively enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…The respective study populations could also differ, although our study sample showed similar age and baseline stroke severity to those reported in previous studies that did demonstrate an association between WUS and AHI. [4][5][6] Our negative finding is consistent with the results found in women in the only prior study that performed a sex-specific analysis. 6 Importantly, the inclusion of strokes with onset during non-nocturnal sleep (naps) added almost 5% to the estimate of WUS in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The respective study populations could also differ, although our study sample showed similar age and baseline stroke severity to those reported in previous studies that did demonstrate an association between WUS and AHI. [4][5][6] Our negative finding is consistent with the results found in women in the only prior study that performed a sex-specific analysis. 6 Importantly, the inclusion of strokes with onset during non-nocturnal sleep (naps) added almost 5% to the estimate of WUS in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The estimate provided by this and some studies 4,6 suggests that WUS is higher (;one-third) than other studies suggest. 3,5 Our result is also in keeping with estimates from the large International Stroke Trial. 11 In this study, participants with WUS had a milder presentation (e.g., more presented fully conscious, and more had lacunar syndromes) than non-WUS participants.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“… 13 14 15 Lower blood pressure was suggested as a risk factor for WUS, 11 but this finding has not been replicated in other studies. Four 12 15 16 17 of six 11 12 13 15 16 17 studies that assessed OSA as a stroke risk factor found that habitual snoring or a higher apnea-hypopnea index in poststroke polysomnography (PSG) was more frequent among WUS patients ( Supplementary Table 1 in the online-only Data Supplement). However, poststroke PSG cannot be used to diagnose preexisting OSA due to the high prevalence of new-onset OSA following acute stroke.…”
Section: Introductionmentioning
confidence: 83%
“…We prospectively evaluated consecutive patients with acute stroke (≤3 days after onset) who were admitted to the First Affiliated Hospital of Chongqing Medical University between April 2017 and December 2017. WUS was defined as the occurrence of new symptoms suggestive of stroke detected upon waking from sleep (regardless of the time of the day), and non-WUS was defined as the occurrence of stroke symptoms during the awake state [21]. Among the 612 patients with acute stroke, we excluded patients with the following criteria: delayed admission more than 3 days after onset (n = 3), stroke mimics (n = 34), other diseases with stroke-like attacks (n = 3), loss to follow-up (n = 17), transient ischemic attacks (defined as stroke symptoms that last <24 h, n = 51), daytime-unwitnessed stroke (n = 29), and hemorrhagic stroke (n = 2).…”
Section: Methodsmentioning
confidence: 99%